Cytokines regulating lymphangiogenesis. (August 2018) - Sáinz-Jaspeado, Miguel; Claesson-Welsh, Lena
Highlights: Lymphatics serve in draining interstitial fluid, in immune surveillance and fat absorption. Lymphangiogenesis denotes formation of new lymphatics from pre-existing vessels. Vascular endothelial growth factor C is an essential stimulator of lymphangiogenesis. Lack of lymphatic function leads to painful and crippling edema. Cancer may be accompanied by lymphangiogenesis, facilitating metastatic spread. Abstract : Lymphatic vessels are established by differentiation of lymphendothelial progenitors during embryogenesis. Lymphangiogenesis, the formation of new lymphatic vessels from pre-existing ones is rare in the healthy adult but takes place during pathological conditions such as inflammation, tissue repair and tumor growth. Conditions of dysfunctional lymphatics exist after surgical interventions or in certain genetic diseases. A key lymphangiogenic stimulator is vascular endothelial growth factor-C (VEGFC) acting on VEGF receptor-3 (VEGFR3) expressed on lymphendothelial cells. Other cytokines may act directly to regulate lymphangiogenesis positively or negatively, or indirectly by inducing expression of VEGFC. This review describes different known lymphangiogenic cytokines, their mechanism of action and role in lymphangiogenesis in health and disease.